Atlas of human anatomy - Netter, Frank H. (Philadelphia : Saunders/Elsevier, 2011)
"The world's most beloved anatomy atlas! Dr. Netter's phenomenal, classic artwork demystifies this often intimidating subject, providing a coherent, lasting visual vocabulary for understanding anatomy and how it applies to medicine."--BOOK JACKET.
Includes index.
Keywords: Human anatomy -- Atlases; Anatomy -- Atlases